Understanding the relationship between states’ unemployment rates and gross domestic product - Alghamdi, Norah (Eximia, 2023)
This research paper examines the factors that affect the unemployment rate in public sector states of America. The study is based on the relationship between states' unemployment rates and Gross Domestic Product (GDP). The research question is: What is the relationship between states' unemployment rates and GDP? The hypothesis is that states with high unemployment rates will have lower GDPs. The research design contains three studies and one theory for different authors in the literature review section relevant to this study. The unit of analysis is the states of America. The paper proposes a methodology that describes the measures of the study. The researcher used nominal-level data to measure states and scale to measure GDP, states' unemployment rate, and population. The study concludes that higher unemployment rates caused lower GDP in states of America. An interesting subject for future study is the effects of states' unemployment rates on the state's GDP.